Ionoregulatory Impairment in African Catfish (Clarias gariepinus) Exposed to Combined Stressors of Lead and Cypermethrin - Omowumi O ADEWALE; Joseph A ADEYEMI (Notulae Scientia Biologicae, 2014)
The contamination of aquatic ecosystem with heavy metals and pesticides has increased dramatically over the years, and this has generated a lot of attention by environmental experts. There are reports on impacts of different single toxicants on aquatic organisms but not much has been done to investigate the impacts of mixtures of toxicants on aquatic life. In this study we investigated the effects of multiple stressors of Pb and cypermethrin on ionoregulation in the African catfish (Clarias gariepinus). Adults C. gariepinus were exposed to either borehole water (control), 2 mg/L Pb, 0.5 μg/L cypermetrin or a mixture of 2 mg/L Pb and 0.5 μg/L cypermethrin for 96 h, after which the levels of plasma Na+, Cl- and K+ were determined as a measure of branchial ionoregulatory disturbance. The exposure of C. gariepinus to 0.5 μg/L cypermethrin resulted in a significant reduction in plasma Na+ (43% decrease) and Cl- (31% decrease) but a 2-fold increase in plasma K+ concentrations. Exposure to a mixture of cypermethrin and Pb resulted in 53% decrease in plasma Na+, 40% decrease in plasma Cl- and a 3- fold increase in plasma K+. There was no significant difference between the control and those exposed to just only 2 mg/L Pb for all the parameters measured. The results of this study indicated that exposure of aquatic organisms to combined stressors of heavy metals pollution as well as pesticide contamination could have a serious effect on the physiology especially on ionic regulation in the exposed fish.